IMPLEMENTASI JALAN KAKI 30 MENIT PADA PASIEN DIABETES MELLITUS TIPE II UNTUK MENGONTROL KADAR GULA DARAH DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN - Winda Khairiana Delima Putri Br Sitepu; Suharto Suharto; Kipa Jundapri (SINERGI : Jurnal Riset Ilmiah, 2026)
Diabetes mellitus is a chronic disease that occurs when the pancreas is unable to produce sufficient insulin or when the body cannot effectively use the insulin produced, resulting in increased blood glucose concentration (hyperglycemia). One non- pharmacological nursing intervention that can be used to reduce blood glucose levels in patients with diabetes mellitus is a 30-minute walking activity. This study aims to describe the implementation of a 30-minute walking intervention to reduce blood glucose levels in patients with diabetes mellitus at TK II Putri Hijau Hospital, Medan. This research used a descriptive case study method with a nursing care approach including assessment, diagnosis, intervention, implementation, and evaluation. The study was conducted in April 2025 on two patients with diabetes mellitus. The results showed that after implementing the 30-minute walking intervention, both patients experienced a decrease in blood glucose levels: in Patient 1. from 245 mg/dL to 134 mg/dL; and in Patient 2, from 234 mg/dL to 164 mg/dL. The conclusion from this implementation indicates that a 30-minute walking intervention can be an effective nursing intervention to help reduce blood glucose levels in patients with diabetes mellitus, as demonstrated in both cases